Dyspeptic Syndrome in Urban Population of Jakarta - Marcellus Simadibrata; Murdani Abdullah; Ari Fahrial Syam; Achmad Fauzi; Dadang Makmun; Chudahman Manan; Abdul Aziz Rani; Aan Santi; Ekowati Rahajeng (The Indonesian Society for Digestive Endoscopy, 2010)
Background: Dyspeptic syndrome is experienced by many patients who visit general practitioners and gastroenterologist. In Indonesia, a small number of epidemiological data about dyspeptic syndrome are available. The aim of this study was to obtain data on prevalence, characteristics and factors/lifestyle associated with dyspeptic syndrome in urban population of Jakarta. Method: The study was conducted by interview to 1,645 respondents representing the population of Jakarta in the year 2007 using the Steps WHO version 1.4 instruments. The selection of respondents was performed by multistage cluster random sampling, i.e. each municipality is represented by one district and each was represented by a number of villages and respondents interviewed at random. Dyspeptic syndrome is defined whenever there is one or more complaints of nausea, vomiting, belching, epigastric pain, no appetite, early satiety, bloating. Scoring was performed for each category of questions using wstep1 method prior to the analysis. Data analysis was performed with Chi-square test or t-test. Results: Of the 1,645 respondents, the prevalence of dyspeptic syndrome was 58.1%. The most apparent clinical complaint ranges consecutively, i.e. nausea 30.1%, epigastric pain 28.7%, bloating 23.8%, etc. Dyspeptic syndrome is significantly more often experienced by female respondents (p 0.001). Dyspeptic syndrome were more common in respondents who have less/no fruit (p 0.001) and vegetables (p = 0.049) intake. Dyspeptic syndrome is more common in respondents with anxiety and depression (p 0.001) also in respondents who consume non-steroidal anti-inflammatory drugs (NSAIDs) (p 0.001). Conclusion: Prevalence of dyspeptic syndrome in Jakarta urban population is 58.1%. Dyspeptic syndrome was more common in female, respondents who have less / no fruit and vegetables intake, in respondents who experienced anxiety and depression and respondents who consume NSAIDs. Keywords: dyspeptic syndrome, Jakarta, urban population, prevalence